Going west? The dissemination of Neolithic innovations between the Bosporus and the Carpathians : proceedings of the EAA Conference, Istanbul, 11 September 2014 - Reingruber, Agathe; Tsirtsoni, Zoï; Nedelcheva, Petranka (Themes in contemporary archaeology, 2017)
Going West?" uses the latest data to question how the Neolithic way of life was diffused from the Near East to Europe via Anatolia. The transformations of the 7th millennium BC in western Anatolia undoubtedly had a significant impact on the neighboring regions of southeast Europe. Yet the nature, pace and trajectory of this impact needs still to be clarified. Archaeologists previously searched for similarities in prehistoric, especially Early Neolithic material cultures on both sides of the Sea of Marmara. Recent research shows that although the isthmi of the Dardanelles and the Bosporus connect Asia Minor and the eastern Balkans, they apparently did not serve as passageways for the dissemination of Neolithic innovations. Instead, the first permanent settlements are situated near the Aegean coast of Thrace and Macedonia, often occurring close to the mouths of big rivers in secluded bays. The courses and the valleys of rivers such as the Maritsa, Strymon and Axios, were perfect corridors for contact and exchange not only in a south-north direction but also the other way round. Using previous studies as a basis for fresh research, this volume presents exciting new viewpoints by analyzing recently discovered materials and by applying modern research methods of interdisciplinary investigations. The seventeen authors of this book have dedicated their research to a renewed evaluation of an old problem: namely, the question of how the complex transformations at the transition from the Mesolithic to the Neolithic can be explained
Keywords: Konferenzschrift; Konferenzschrift -- 11.09.2014 -- Istanbul; Innovation; Neolithikum; Karpaten; Bosporus-Gebiet